Incident atrial fibrillation among Asians, Hispanics, blacks, and whites - Dewland, Thomas A; Olgin, Jeffrey E; Vittinghoff, Eric; Marcus, Gregory M (Circulation (New York, N.Y.), 2013)
Because the association between atrial fibrillation (AF) and race has only been rigorously compared in population-based studies that dichotomized participants as white or black, it is unclear whether white race confers elevated AF risk or black race affords AF protection. The Healthcare Cost and Utilization Project was used to identify patients receiving hospital-based care in California between January 1, 2005 and December 31, 2009. The association between race and incident AF was examined using Cox proportional hazards models. Interaction analyses were performed to elucidate the mechanism underlying the race-AF association. Among 13 967 949 patients, 375 318 incident AF episodes were observed over a median 3.2 (interquartile range 1.8-4.3) years. In multivariable Cox models adjusting for patient demographics and established AF risk factors, blacks (hazard ratio, 0.84; 95% confidence interval, 0.82-0.85; P<0.001), Hispanics (hazard ratio, 0.78; 95% confidence interval, 0.77-0.79; P<0.001), and Asians (hazard ratio, 0.78; 95% confidence interval, 0.77-0.79; P<0.001) each exhibited a lower AF risk compared with whites. AF risk among whites was disproportionately higher in the absence of acquired cardiovascular risk factors and diminished or reversed in the presence of comorbid diseases. Although Hispanics and Asians also had a lower adjusted risk of incident atrial flutter compared with whites, the risk of flutter was significantly higher among blacks. In a large hospital-based cohort, whites have an increased risk of AF whether compared with blacks, Asians, or Hispanics. The heightened AF risk among whites is most pronounced in the absence of cardiovascular comorbidities.